Analisis Peran Gender dalam Pengasuhan Anak pada Keluarga Etnis Jawa dan Sunda di Wilayah Perbatasan - Noeranisa Adhadianty Gunawan; Nunung Nurwati; Bintarsih Sekarningrum (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study aims to analyze gender roles in childcare of families in Jawa-Jawa Ethnic, Jawa-Sunda Ethnic, and SundaSunda Etnic. Javanese-Javanese Ethnic and Sundanese-Sundanese Ethnic family as the main study that will show a mixture of values, culture, and behavior in Javanese-Sundanese Ethnic families. The study uses qualitative descriptive to approach with the case study research techniques. Data collection was obtained through observation, interviews, research studies and documentation studies. The results of the study shows that the differences gender roles in childcare of the Javanese-Javanese ethnic families, the Sundanese-Sundanese ethnic families, and the JavaneseSundanese ethnic families caused by habits, the way of life, and values are still embraced by each family. Based on the culture of its respective ethnicity The role of gender in the family is functioning but there is also a dysfunction where one of the roles are not practiced by men or women in parenting. Thus, it is, although the two ethnicities have coexisted for decades, the people still see differences in childcare caused by the application of the values in each family.